PELATIHAN PENGGUNAAN SMART APPLICATION BERBASIS TPACK DALAM PROSES DAN EVALUASI PEMBELAJARAN IPA FISIKA UNTUK GURU DI TANGERANG SELATAN - Zakirman, Zakirman; Ekawati, Ratna; Safitri, Heni; Widiasih, Widiasih; Ichwan, Ichwan (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Changes in learning patterns that are taking place rapidly due to Covid-19 have made every educational institution able to quickly adapt, especially in the use of learning technology. Teacher readiness in optimizing the use of technology to support the learning process is a new problem that arises when the concept of digital learning begins to be echoed. The use of technology can help teachers visualize material (such as in science learning Physics) and assist teachers in conducting evaluation activities in a practical and efficient manner. The limitations of teachers, especially in several educational institutions in South Tangerang to utilize technology in learning, are the background of the importance of training activities carried out. The results obtained after implementation refer to the evaluation of tasks and practices observed during the training process, indicating that there was an increase in teacher skills in utilizing technology to support the learning process. The teachers who have attended the training have been able to integrate the use of virtual laboratory applications and evaluate student learning outcomes using the quizizz application. The training on the use of learning technology is one of the forms of support from the Physics Education Study Program of FKIP UT to assist and assist teachers in carrying out technology-based learning activities, especially in Physics Science learning during the Covid-19 pandemic.